Analisis Yuridis Money Politic oleh Calon Anggota Dewan Perwakilan Daerah dalam Pemilihan Umum - Ade Marcelian Pande; Ida Ayu Putu Widiati; I Wayan Arthanaya (Warmadewa Press, 2021)
Money politics is a crime against democracy as aspired by the Indonesian state, especially against money politics crimes committed by Regional Representative Council Candidates. This study aimed to examine the forms of money politics in general elections and to reveal sanctions against candidates for Regional Representative Council Candidates who committed money politics. This study is normative research with a statutory approach. The sources of data used were primary and secondary data. Data were collected through reading activities, which were carried out by collecting existing legal materials or studying documents from existing laws and regulations and other supporting instruments. The results of the study indicated that the regulation of money politics is regulated in the constitution and some special legal regulations. The form of money politics is in the form of money, public facilities, basic needs, and projects. The sanctions applied are imprisonment and fines or imprisonment instead of fines. Criminal sanctions are applied to perpetrators who gave or received all forms of money politics, which is used as a strategy to win political contestations